Common allergens prevalent in and around Ambala, Haryana: An intradermal study among patients with asthma and allergic rhinitis and atopic dermatitis - Dinesh Mehta; Abinav Dagar; Jai Kishan; Parwinder Singh; Tushar Nehra; Himanshu Sharma (Wolters Kluwer Medknow Publications, 2018)
Objective: Identification of allergens by intradermal test in patients with asthma, allergic rhinitis, and eczema. Materials and Methods: Intradermal test was performed in 100 patients of Ambala over an 8-year period to identify the common allergens. A total of 197 allergens including 50 types of pollen, 19 fungi, 17 insects, 14 types of dust, 6 animal dander, 7 types of fabric and feather and 82 types of foods, dust mite, and parthenium were tested. Results: In this study, the major allergens were pollen (51%) followed by foods (28.9%), insects (26.9%), fungus (12.6%), dusts (6.7%). Among pollen allergens, Brassica campestris (8%) was a major allergen followed by Ageratum conyzoides (7%) and Artemisia scoparia (6%) Cannabis sativa, Cynodon dactylon and Maerua arenaria (5%). Among the fungal group, Alternaria tenuis, Aspergillus flavus, Aspergillus fumigates, Candida albicans, Penicillium sp., Rhizopus nigricans (3%), Fusarium solani (2%) were found. In the insect group, mosquito (7%), ant (6%), grasshopper (5%), locust (male), moth, and house fly (4%) were the major allergens. Among the dust allergens, grain dust rice (3%), straw dust, house dust, and grain dust bajra (2%) were found. Among the food allergens, prawn (5%), almonds, Baker's yeast, Bengal gram (3%) and mushroom, mango ripe, rajma, cinnamon, chocolate, beans fresh, and areca nut (2%) were found. Conclusion: It can be said that the knowledge may help to create a mapping of allergens in this area and help to treat patients by immunotherapy or avoidance strategy.